Preparation of Hydroxypropyl Cyclosophoraose/Dextran Microspheres for the Controlled Release of Ciprofloxacin - Lee, Benel; Jeong, Daham; Joo, Sang-Woo; Choi, Jae Min; Lee, Jae Yung; Cho, Eunae; Park, Seyeon; Jung, Seunho (Bulletin of the Korean Chemical Society, 2016)
Hydroxypropyl cyclosophoraose/dextran (HPCys/dextran) microspheres were prepared using an emulsion polymerization method for use as drug carriers to achieve the controlled release of a poorly water‐soluble antibacterial drug, ciprofloxacin (CFX). Cyclosophoraoses are cyclic (1 → 2)‐β‐d‐glucans isolated from the Rhizobium species. Characteristics of HPCys/dextran microspheres were investigated using Fourier transform infrared analysis, solid‐state 13C nuclear magnetic resonance spectroscopy, and field emission scanning electron microscopy. The amount of CFX released from these microspheres at pH 7.4 (intestinal phase pH) was about two times higher than that released at pH 1.2 (gastric phase pH). Furthermore, HPCys/dextran microspheres did not show any toxicity in human embryonic kidney cells. We propose that HPCys/dextran microspheres could be used as an effective pH‐dependent release system for poorly water‐soluble drugs such as CFX.